2022
DOI: 10.3390/antiox11112282
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Dietary β-Glucan Levels on Antioxidant Capacity and Immunity, Gut Microbiota and Transcriptome Responses of White Shrimp (Litopenaeus vannamei) under Low Salinity

Abstract: β-Glucan could significantly improve the antioxidant capacity of aquatic animals. The effects of different dietary levels (0 (control), 0.05, 0.1, 0.2 or 0.4%) of β-glucan on the growth, survival, antioxidant capacity, immunity, intestinal microbiota and transcriptional responses of Litopenaeus vannamei under low salinity (≤3) were investigated. The dietary growth trial lasted 35 days (initial shrimp 0.26 ± 0.01 g). The results indicated that the growth performance of the 0.1% and 0.2% groups was significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 58 publications
3
18
0
Order By: Relevance
“…Here, β-1,3-glucan supplementation did affect the intestinal microbiota and significantly increased the microbial diversity in white shrimp. Similar results were also observed in tilapia ( 21 ), carp ( Cyprinus carpio ) ( 37 ) and white shrimp from a recent study ( 22 ). Although the composition of the intestinal microbial community can be dramatically affected by the diets, the core microbiota is essentially stable in the host ( 38 ).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Here, β-1,3-glucan supplementation did affect the intestinal microbiota and significantly increased the microbial diversity in white shrimp. Similar results were also observed in tilapia ( 21 ), carp ( Cyprinus carpio ) ( 37 ) and white shrimp from a recent study ( 22 ). Although the composition of the intestinal microbial community can be dramatically affected by the diets, the core microbiota is essentially stable in the host ( 38 ).…”
Section: Discussionsupporting
confidence: 87%
“…Total number of edges 3847 4743 also observed in tilapia (21), carp (Cyprinus carpio) (37) and white shrimp from a recent study (22). Although the composition of the intestinal microbial community can be dramatically affected by the diets, the core microbiota is essentially stable in the host (38).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…As the intestine of L. vannamei is not just involved in nutrient absorption but also related to immune capacity, the changes in the composition of the microbiota may cause diseases and increase mortality [ 43 ]. Previous studies have reported that environmental stress [ 44 , 45 ] and prebiotics [ 46 , 47 ] could induce a significant impact on the α-diversity of intestinal microbiota in shrimp. In this study, the alpha diversity of intestine microbiota was changed under the stress of low salinity and antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatopancreas are important detoxigenic organs and the first barrier against the interference of the whole organism (Pawert et al, 1996;Opstvedt et al, 2000;. However, only a few studies have combined molecular and biochemical procedures to describe the relationship between the transcription of specific immune and antioxidant genes and their activity (Qiu et al, 2018;Chen et al, 2021;Qiao et al, 2022), and the response mechanism of shellfish to residual chlorine stress is also rarely studied.…”
Section: Introductionmentioning
confidence: 99%